Proceedings of the American Mathematical Society. Volume 131, Number 3, 2003 - American Mathematical Society (American Mathematical Society, 2009)
On the local spectral radius of positive operators Miroslawa Zima Proc. Amer. Math. Soc. 131 (2003), 845-850. Abstract, references and article information Retrieve article in: PDF